A Single-center Prospective Observational Study Investigating the Accuracy of Preoperative Diagnostic Procedures in the Assessment of Lymph Node Metastases in Nonfunctioning Pancreatic Neuroendocrine Tumors. Issue 5 (5th November 2022) - Partelli, Stefano; Muffatti, Francesca; Andreasi, Valentina; Giannone, Fabio; Rossi, Gemma; Palumbo, Diego; Mapelli, Paola; Schiavo Lena, Marco; Arcidiacono, Paolo Giorgio; De Cobelli, Francesco; Picchio, Maria; Doglioni, Claudio; et al.
Abstract : Objective: To determine the accuracy of preoperative imaging, including contrast-enhanced computed tomography (CE-CT), endoscopic ultrasound (EUS), and 68 Gallium-DOTATOC positron emission tomography ( 68 Ga-DOTATOC PET), in identifying nodal metastases (N+) in sporadic nonfunctioning pancreatic neuroendocrine tumors (NF-PanNETs). Background: An accurate preoperative identification of N+ in NF-PanNETs is critical for surgical planning. The accuracy of different imaging techniques in detecting lymph node (LN) metastases in NF-PanNETs has been poorly investigated. Methods: All consecutive patients undergoing surgery for sporadic NF-PanNETs (2018–2021) were enrolled in a prospective study (DETECTYON; NCT03918759). The accuracy of preoperative imaging techniques in detecting N+ was assessed through sensitivity, specificity positive and negative predictive values. Results: Overall, 100 patients with NF-PanNETs underwent CE-CT, EUS, and 68 Ga-DOTATOC PET before pancreatic resection. LN metastases were found in 42 cases (42%). Sensitivity, specificity, positive predictive value, and negative predictive value of different imaging techniques were 26%, 95%, 79%, 64% for CE-CT, 19%, 98%, 89%, 63% for EUS, and 12%, 95%, 63%, 60% for 68 Ga-DOTATOC PET, respectively. Radiologic tumor size >4 cm and the presence of radiologic N+ at ≥1 imaging were independent predictors of N+ at pathology. The identification of N+ at ≥1 imaging technique was associated with a higher number of positive LNs compared with negative imaging (4 vs 2) ( P =0.012). Conclusions: CE-CT, EUS, and 68 Ga-DOTATOC PET are poorly sensitive in predicting nodal status in NF-PanNETs despite a high specificity.